2022
DOI: 10.3390/v14112491
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue ‘Viral Infection and Autoimmune Diseases’

Abstract: Viral infection, which is one of the environmental factors, and human autoimmune diseases are often associated with each other [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The observed causal relationship between critical COVID-19 and increased susceptibility to celiac disease illuminates the multifaceted consequences of viral infections on the immune system and autoimmune disorders [30]. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus responsible for COVID-19, has been shown to exert profound effects on lymphocytes [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…The observed causal relationship between critical COVID-19 and increased susceptibility to celiac disease illuminates the multifaceted consequences of viral infections on the immune system and autoimmune disorders [30]. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus responsible for COVID-19, has been shown to exert profound effects on lymphocytes [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Most symptoms of long‐COVID‐19 syndrome are debilitating but not fatal 8 ; however, some sequelae can be serious and require medical care. COVID‐19 affects both the innate and adaptive immune systems; indeed, virus‐triggered hyperactivation of helper T cells and antigen‐presenting cells causes dysfunction of various organs and systems 4,6,9 . SARS‐CoV2 mutates quickly, resulting in the rapid emergence of variants, each of which may interact with the immune system in different ways 10 …”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 affects both the innate and adaptive immune systems; indeed, virus-triggered hyperactivation of helper T cells and antigen-presenting cells causes dysfunction of various organs and systems. 4,6,9 rapid emergence of variants, each of which may interact with the immune system in different ways. 10 A study in Hong Kong showed that the risk of pernicious anemia, SpA, RA, other autoimmune arthritis, psoriasis, pemphigoid, Graves' disease, anti-phospholipid antibody syndrome, immune-mediated thrombocytopenia, multiple sclerosis, and vasculitis was significantly higher in patients with COVID-19 than in those without.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactivation of HSV-1 triggers a range of antiviral responses, potentially leading to the disruption of immune homeostasis [42]. An increasing number of researchers are displaying heightened interest in investigating the effects of viruses on autoimmune diseases [43], thereby opening up new avenues for future research into the underlying mechanisms of autoimmune disorders.…”
Section: Discussionmentioning
confidence: 99%